Feasibility Study of a Custom-made Film for End-to-End Quality Assurance Test of Robotic Intensity Modulated Radiation Therapy System - Kim, Juhye; Park, Kwangwoo; Yoon, Jeongmin; Lee, Eungman; Cho, Samju; Ahn, Sohyun; Park, Jeongeun; Choi, Wonhoon; Lee, Ho (Progress in Medical Physics, 2016)
This paper aims to verify the clinical feasibility of a custom-made film created by a laser cutting tool for End-to-End (E2E) quality assurance in robotic intensity modulated radiation therapy system. The custom-made film was fabricated from the Gafchromic EBT3 film with the size of 8”×10” using a drawing that is identical to the shape and scale of the original E2E film. The drawing was created by using a computer aided design program with the image file, which is obtained by scanning original E2E film. Beam delivery and evaluations were respectively performed with the original film and the custom-made film using fixed-cone collimator on three tracking modes: 6D skull (6DS), Xsight spine (XS), and Xsight lung (XL). The differences between total targeting errors of the original and custom-made films were recorded as 0.17 mm, 0.3 mm, and 0.17 mm at 6DS, XS, and XL tracking modes, respectively. This indicates that the custom-made film could yield nearly equivalent results to those of the original E2E film, given the uncertainties caused by distortions during film scanning and vibrations associated with film cutting. By confirming the clinical feasibility of a custom-made film for E2E testing, it can be expected that economic efficiency of the testing will increase accordingly. KCI Citation Count: 1